Conventional and Islamic Letter of Credit: Comparison and Implementation - Atharyanshah Puneri (Airlangga International Journal of Islamic Economics and Finance, 2021)
This study attempts to provide the insight about payment method in international trade, especially by using Letter of Credit both conventional way and Islamic way. This study is exploratory and using qualitative method of research. This study reviews and analyses the previous literatures and other secondary data to conduct the study. The secondary data for this research were gathered through library research. This study also doing the document analysis. Based on the data collected, Letter of Credit is the most secured and commonly used as the method of payment for International Trade. But a lot of contents on the Conventional Letter of Credit is not Shariah-compliant. Islamic Financial Institutions around the world trying to comes up with Islamic Letter of Credit, but to implementing Islamic Letter of Credit creates some new issues and challenges. This study attempts to provide the insight about payment method in international trade, especially by using Letter of Credit both conventional way and Islamic way.